The effect of three lining materials on microleakage of packable composite resin restorations in young premolars with cavity margins located on enamel and dentin/cementum - An In vitro study - Rizk, Hazim Mohamed; Al-Ruthea, Mohammed; Habibullah, Mohammed Ali (International Journal of Health Sciences, 2018)
Objectives: The objective of our in vitro investigation was to assess the effect of a layer of three lining materials; flowable composite, flowable compomer, and light-curing glass ionomer cement as a liner on microleakage with Class V packable composite restorations in young premolar teeth. Materials and Methods: A total of 40 premolars were assigned randomly into four groups of 10 teeth each (Groups 1, 2, 3, and 4). Class V cavities (3 mm × 2 mm × 1.5 mm) were prepared in a standardized technique on the buccal surface of every tooth with the cervical margin extending 0.5 mm below the cementoenamel junction, into the dentin. Cavities in the first group (control group) were filled with packable composite (Heliomolar HB) without liners. Cavities in Groups 2, 3, and 4 were restored with packable composite after placing flowable composite (Heliomolar Flow), light-curing glass ionomer cement (Vivaglass), and flowable compomer (Compoglass Flow) as liners, respectively. The 40 restored teeth were put in thermocycling machine, then immersed in 2% methylene blue solution for a period of 24 h to permit penetration of methylene blue into potential microgaps that might have been created between the restorative material and the tooth. Each tooth was then cut buccolingually into two halves through the center of the restoration parallel to their long axes. Photomicrographs of each group were captured, then examined using the ImageJ an analysis software. Results: Control group (packable composite), Group 2 (flowable composite), and Group 3 (light-curing glass ionomer cement) showed no statistical significance between them. The difference between control group (packable composite) and Group 4 (flowable compomer) was statistically significant. Conclusions: Flowable compomer as intermediate lining material can significantly reduce microleakage under packable composite.